Restoring broken things : what happens when we catch a vision for the new world Jesus is creating - Chapman, Steven Curtis; Smith, Scotty, 1950- (Nashville : Integrity Publishers, 2005)
"Practical implications of Jesus' commitment to make all things new and the part we are to play with Him in this redemptive process"--Provided by publisher.
Includes bibliographical references (p. 253-254).
Keywords: Jesus Christ; Reconciliation -- Religious aspects -- Christianity; Christian life; Redemption -- Christianity